Rights technologies and online content business models - Rosenblatt, Bill (Henry Stewart Talks, 2010)
Why rights technologies?, DRM: Controlling Access to Content, DRM is a troubled technology... why?, Content Identification, Watermarking, Fingerprinting, Content Identifiers, Rights Expression Languages, Rights Information Management, Future possibilities for rights technologies